Aldehyde Dehydrogenase 1 making molecular inroads into the differential vulnerability of nigrostriatal dopaminergic neuron subtypes in Parkinson’s disease - Cai, Huaibin (Transl Neurodegener, 2014)
A preferential dysfunction/loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc) accounts for the main motor symptoms of Parkinson’s disease (PD), the most common degenerative movement disorder. However, the neuronal loss is not stochastic, but rather displays regionally selectivity, indicating the existence of different DA subpopulations in the SNpc. To identify the underlying molecular determinants is thereby instrumental in understanding the pathophysiological mechanisms of PD-related neuron dysfunction/loss and offering new therapeutic targets. Recently, we have demonstrated that aldehyde dehydrogenase 1 (ALDH1A1) is one such molecular determinant that defines and protects an SNpc DA neuron subpopulation preferentially affected in PD. In this review, we provide further analysis and discussion on the roles of ALDH1A1 in the function and survival of SNpc DA neurons in both rodent and human brains. We also explore the feasibility of ALDH1A1 as a potential biomarker and therapeutic target for PD.